Aplicación de un sistema de costos por órdenes de producción en productos lácteos “San José” de la provincia de Tungurahua cantón Santiago de Pillaro parroquia Rocafuerte durante el cuarto trimestre del año 2014 - Caisaguano Basantes, Silvia Liliana (2015)
This research was conducted in San Jose Dairy Products which was determined as the main problem that a complaint to the economic, accounting and production activities due to the lack of a cost system, leading to ignore their actual costs manufacturing and therefore its profitability, putting a company in a little competitive position due to lack of sound decision making by management. To do this by pre and taking into account the proposal and study objectives were selected and applied methods and research techniques such as survey and interview, which allow to obtain reliable and relevant to the job execution information….